Efficacy analysis of high-intensity laser therapy for post lumbar surgery syndrome - Ruizhao Zhao; Junjie Qiao; Xinyao Lv; Xiutong Fang (Scientific Reports)
Abstract This retrospective cohort study investigated the efficacy of high-intensity laser therapy (HILT) in patients with the Post-Lumbar Surgery Syndrome (PLSS). The study analyzed patients diagnosed with PLSS who were admitted to our hospital between 2020 and 2023. In this study, patients were grouped by past treatment: Group A (oral medication) and Group B (high-intensity laser therapy plus oral medication).We conducted a comprehensive review of medical records to compare longitudinal outcomes, including visual analog scale (VAS) scores of low back pain, Oswestry Disability Index (ODI) assessments, and paraspinal muscle fat infiltration levels. Data were extracted at multiple time points: pre-treatment baseline, as well as post-treatment intervals of one week, one month, three months, six months, and twelve months. At 3-month and 6-month post-treatment, VAS scores of Group B were significantly lower than those of Group A (P < 0.001). At 12-month post-treatment, the ODI of Group B was significantly lower than that of Group A (P < 0.05). In patients of Group B, HILT may demonstrate a positive effect on the lumbar paraspinal muscles fat infiltration (PMFI) (P < 0.001). HILT demonstrates efficacy in alleviating clinical symptoms of PLSS and represents a viable adjuvant therapy for symptom management.